Premeditatio Malorum and Dissemination of Hope in Post-Pandemic Recovery - Pasopati, Rommel; Yuliastuti, Anicleta; Pujimahanani, Cahyaningsih (UIN Sunan Ampel Surabaya, 2022)
Premeditatio malorum is a Stoic philosophical concept that speaks about negative visualization of conditions that may come. By imagining, Stoic people could prepare anything to the most specific aspects that may be realized. Meanwhile, post-pandemic condition is related to recovery of everything. Since COVID-19 outbreak changes our life, new normal condition should be filled with preventive actions rather than preemptive ones. Alongside with those, prolonging hope should be always kept in flowing to walk together with people in everyday life. The question is, how may premeditatio malorum contribute to dissemination of hope in post-pandemic recovery today? Using qualitative method, philosophical and cultural concepts are used to explain correlations between premeditatio malorum, living hope, and post-pandemic recovery. The reality of hope does not stand alone but should be accompanied with anticipations of bad impacts that may come. Preparing for inevitable setbacks could contribute more to optimism than being pessimistic or surrender to current conditions. It is matter of practice that will make people calm and shape further hope to amend unavoidable impacts. In conclusion, by thinking negatively, this Stoic concept could overcome negative impacts of future condition. Moreover, premeditatio malorum may provide such framework of thoughts to widen hope to its best and worst conditions that may happen afterwards.